Condroblastoma benigno do osso occipital: Relato do caso Benign chondroblastoma of the occipital bone: case report - João Flávio Mattos Araújo; Guilherme Contatore Bierrenbach De Castro; Maria Gracia Iafigliola; Roque José Balbo (Arquivos de Neuro-Psiquiatria)
Condroblastoma benigno é tumor ósseo raro, tendo como origem células cartilagíneas. Classicamente este tumor acomete regiões epifisárias de ossos longos, sendo incomum o envolvimento de ossos do crânio, principalmente o osso occipital. Relatamos o caso de uma paciente com 16 anos de idade, com o diagnóstico de condroblastoma benigno do osso occipital e discutimos os principais aspectos deste tumor. Benign chondroblastoma is a rare bone tumor of immature cartilage cell derivation. This lesion classically occur at the ends of long bones in young persons. Chondroblastoma arising from the occipital bone is extremely rare. We report the case of a 16 year old girl with a benign condroblastoma in the occipital bone, and discuss the clinical, radiological and treatment aspects of this tumor.